Penerapan Teknik Self Management Untuk Menurunkan Prokrastinasti Akademik - Ragil Oneng Prahasdini; Awang Setiawan Wicaksono (Universitas Palangka Raya, 2024)
Academic procastination is an activity of delaying tasks or work, from starting to completing academic-related tasks, which is done intentionally and repeatedly. The research aims to determine and reduce the level of academic procrastination using self-management techniques. This research uses a quantitative method by distributing questionnaires to students, the questionnaire given contains 36 items using a Likert scale. After conducting a pre-test, the researchers found 7 students out of 36 students who had high procrastination scores. An intervention was carried out on 7 students using self-management techniques. Then a post-test was given to find out whether there was a decrease in high procrastination scores after being given the intervention. There are positive results that there is a decrease in the value of academic procrastination as seen from the results of the pre-test and post-test.